Ketidakstabilan Perekonomian Bagi Pelaku Usaha Mikro Kecil dan Menengah (UMKM) Dimasa Covid-19 - Aisi, Okta Khusna (At-Tasyri': Jurnal Hukum dan Ekonomi Syariah, 2021)
The criteria for businesses that are included in MSMEs have been regulated in a legal umbrella based on law. From the research results, it can be concluded that the Government has issued several policies related to the economic slowdown due to the Covid-19 outbreak, namely by providing incentives in the tourism sector, adding more days to leave together, and reducing debt payments for MSME players. In addition, the government opened a call center to receive reports and complaints from cooperatives and MSMEs affected by the Covid-19 outbreak. In addition, the government also needs to provide a stimulus to maintain people's purchasing power in the midst of this crisis so that the benefits provided to the economy can be felt. The stimulus can take the form of reducing electricity rates and reducing fuel prices. The availability of production materials such as raw materials also needs to be guaranteed so that MSME business activities are not significantly disrupted and are able to return to normal production levels as quickly as possible. The efforts that have been made by the government, it seems that many are still focused on the tourism sector which has a major influence on the MSME sector, besides that the leniency of credit is also considered appropriate to ease the burden on MSMEs. However, assistance / incentives to MSMEs, especially micro and small businesses, still need to be considered, especially considering the current social distancing appeal which has a big impact on small and micro businesses that still require a lot of face to face.